Beyond the Individual: A Group-Based Career Development Intervention Implemented in Resource-Constrained Schools in South Africa. Issue 1 (2nd January 2021) - Rabie, Stephan; Visser, Michelle; Naidoo, Anthony; van den Berg, Francois; Morgan, Brandon
ABSTRACT: In South African high schools, many learners have limited support in making career related decisions to prepare them for the world of work after school. An important early transition for career-related decision-making is at the end of Grade 9 when learners are expected to decide which subjects they will select for the last phase of high school. Grade 9 is also the juncture where adolescents may decide to exit their formal schooling and enter the labor market. To support Grade 9 learners in making informed career-related decisions, this study examined the effectiveness of a group-based career guidance intervention implemented in eight secondary schools located in resource-constrained communities in the Western Cape, South Africa. The intervention aimed to improve learners' career decision-making readiness and aid in making subject choices and subsequent career choices. The intervention consisted of interest assessment conducted in a group-format with the learners, after which a workshop was facilitated to share relevant information pertaining to their interests, other career attributes and pending subject choices. The results of this study demonstrate a significant impact of early adolescents' career adaptability and ability to engage in the career decision-making process. These results show promise in the implementation of group-based career intervention, supporting learners to make informed decisions in relation to their career paths.